FRI0077 Adherence To Disease Activity Score Steered Treatment Protocols in Early Arthritis Patients. (15th July 2016) - Akdemir, G.; Markusse, I.M.; Ronday, H.K.; Speyer, I.; Harbers, J.B.; Kerstens, P.J.S.M.; Lems, W.F.; Huizinga, T.W.J.; Allaart, C.F.
Abstract : Background: Adherence to treatment-to-target in early arthritis patients may be target dependent. Objectives: To compare physicians' adherence to treatment protocols targeted at Disease Activity Score (DAS)≤2.4 or <1.6. Methods: The BeSt study compared 4 treatment strategies in 508 early rheumatoid arthritis (RA, 1987 criteria) patients, 3-monthly targeted at DAS≤2.4. Seven years later in roughly the same clinic, the IMPROVED study started with induction therapy in 479 early RA (2010 criteria) and 122 undifferentiated arthritis (UA) patients, followed by 2 treatment arms 4-monthly targeted at DAS remission (<1.6). DAS were measured by trained nurses. Physicians adjusted treatment according to the DAS. We evaluated physicians' adherence to the protocols and assessed associated opinions and conditions during 4 years by Generalized Linear Mixed Models. Results: Protocol adherence (PA) over 4 years was higher in BeSt than in IMPROVED (mean over time 88% and 73%, respectively). PA decreased over time in both studies from 100% to 77% (BeSt) and to 61% (IMPROVED). Protocol violations (PV) were against treatment intensification/restart 47% in BeSt vs 67% in IMPROVED and against treatment tapering/discontinuation (42% vs 33%). If physicians did not intensify/restart, measured DAS was median 0.7 (IQR0.3;1.3) above ≤2.4 (BeSt) and 0.5 (IQR 0.2;0.8) above <1.6 (IMPROVED). If they did not taper/stop, measured DAS was 0.7 (-1.2;-0.3) lower than ≤2.4 (BeSt) and 0.6 (-0.9;-0.3) lower than <1.6 (IMPROVED). In BeSt the odds ratio (OR) for PV were higher if physicians were not satisfied with the current treatment effect 1.4 (95% CI 1.0;1.9), however in IMPROVED this was associated with less PV 0.6 (0.5;0.7) (figure ). Disagreement with DAS was reported slightly more often in IMPROVED than in BeSt (mean over time 18% vs 13%). In both studies the odds for PV were higher if physicians disagreed with the DAS or with the next treatment step and if the visual analogue scale general health of the patient (VASpt) was ≥20 mm higher than that of the physician (VASph). In IMPROVED PV was also higher if the swollen joint count (SJC) was ≤1 but tender joint count (TJC)≥2 (3.0 (2.6;3.4)) or erythrocyte sedimentation rate (ESR) ≥28 (1.7 (1.3;2.1)), or VASpt ≥20 (2.1 (1.8;2.3)). Conclusions: Adherence to DAS steered treatment protocols was high, but PV increased over 4 years. This increase was more distinct in a DAS<1.6 steered protocol, where PV were more likely if the physician disagreed with the measured DAS. This was more often against required treatment intensification than against required tapering, whereas with a target DAS≤2.4 this was balanced. Also, in a DAS<1.6 steered protocol PV occurred more often in case of potential discrepancies between detected joint swelling, pain and ESR. In a DAS≤2.4 steered protocol there were more PV if physicians were not satisfied with the current treatment effect, however in a DAS<1.6 steered protocol this was associated with less PV. These results may indicate that adherence to DAS steered protocols appears to depend at least in part on the height of the target, and in addition on how physicians feel the DAS reflects RA activity. Disclosure of Interest: G. Akdemir: None declared, I. M. Markusse: None declared, H. K. Ronday: None declared, I. Speyer: None declared, J. B. Harbers: None declared, P. J. S. M. Kerstens: None declared, W. F. Lems: None declared, T. W. J. Huizinga: None declared, C. F. Allaart Grant/research support from: Year 1 of the IMPROVED study was sponsored by Abbott. The BeSt study was designed by the investigators and supported by a government grant from the Dutch Insurance Companies, with additional funding from Schering-Plough B.V. and Janssen B.V. Data collection, trial management, data analysis and preparation of the manuscript were performed by the authors.